Exploring Asymmetric Nexus Between Tourism, Economic Growth and CO2 Emissions in the Context of Pakistan - Rehman, Alam; Ishaque, Amir; Malik, Shumaila; Rehman, Shams Ur; Hussain, Arif; Khan, Muhammad; Zeeshan, Muhammad; Afridi, Fakhr E. Alam (International Journal of Energy Economics and Policy, 2021)
This study aims to examine the nexus between tourism, economic growth, and CO2 emissions in Pakistan. We examined the asymmetric relationship between tourism, economic growth, and CO2 emissions for the period 1991 to 2019. We applied NARDL technique, and Granger Causality to predict results. Moreover, we also employed ADF, PP unit root test, Zivot and Andrews test for structural breaks. The nonlinear autoregressive distributed lag is the most appropriate econometric estimator in the case if asymmetric association exists among the variables. The NARDL technique is capable to discover the dynamic association between economic growth, tourism, and CO2 emissions. Our results confirmed the asymmetric nexus between tourism, GDP and CO2 emissions in the context of Pakistan. The results reported that in the short run as well as long run positive and negative shocks of tourism and GDP affect CO2 emissions. The outcomes also revealed unidirectional causality between tourism and CO2 emission, while bi-directional causality between economic growth and CO2 emissions. Likewise, a bi-directional causality has also been reported between tourism and economic growth. The results are very useful for the macro level policy makers in Pakistan, and hopefully will provide significant insight to the relevant stakeholders. Keywords: Tourism, CO2 Emissions, Economic growth, NARDL, Pakistan JEL Classifications: L83, Q13, B41 DOI: https://doi.org/10.32479/ijeep.10929